2021
DOI: 10.1111/obr.13324
|View full text |Cite|
|
Sign up to set email alerts
|

Does prepregnancy weight change have an effect on subsequent pregnancy health outcomes? A systematic review and meta‐analysis

Abstract: International guidelines recommend women with an overweight or obese body mass index (BMI) aim to reduce their body weight prior to conception to minimize the risk of adverse perinatal outcomes. Recent systematic reviews have demonstrated that interpregnancy weight gain increases women's risk of developing adverse pregnancy outcomes in their subsequent pregnancy. Interpregnancy weight change studies exclude nulliparous women. This systematic review and meta-analysis was conducted following MOOSE guidelines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 88 publications
(224 reference statements)
2
35
2
1
Order By: Relevance
“…A recent systematic review and meta-analysis pooling 61 studies investigating outcomes of interpregnancy weight changes from 11 Western countries highlighted the gaps and clinical needs. 10 Data from this meta-analysis showed that women with interpregnancy weight gain had increased risks of gestational diabetes, hypertensive disorders, large-forgestational-age birth and caesarean delivery, while those with interpregnancy weight loss had increased risks for preterm delivery and small-for-gestational-age birth. In the present study, our aims were to (i) describe the distribution of weight changes in BMI between first and second pregnancies among Singaporean women and (ii) examine whether similar associations between interpregnancy BMI changes and pregnancy outcomes would be observed in Asian women, compared to those reported in the aforementioned meta-analysis among Caucasians.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…A recent systematic review and meta-analysis pooling 61 studies investigating outcomes of interpregnancy weight changes from 11 Western countries highlighted the gaps and clinical needs. 10 Data from this meta-analysis showed that women with interpregnancy weight gain had increased risks of gestational diabetes, hypertensive disorders, large-forgestational-age birth and caesarean delivery, while those with interpregnancy weight loss had increased risks for preterm delivery and small-for-gestational-age birth. In the present study, our aims were to (i) describe the distribution of weight changes in BMI between first and second pregnancies among Singaporean women and (ii) examine whether similar associations between interpregnancy BMI changes and pregnancy outcomes would be observed in Asian women, compared to those reported in the aforementioned meta-analysis among Caucasians.…”
Section: Introductionmentioning
confidence: 89%
“…7,8 However, the extent to which interpregnancy weight change influences the risks of subsequent maternal and neonatal outcomes remain poorly understood, 9 and most studies have been focused on Western populations. 10 Given that Asians have increased health risks at different BMI thresholds to Caucasians, 11 and that unique sociocultural factors may influence weight management behaviours before, during, and after pregnancy, 10 it is essential to personalize weight management planning for Asian women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of children and adolescents with obesity has risen to 124 million worldwide and could exceed 250 million by 2030 without substantial interventions 4. A meta-analysis of 61 studies showed that increased preconception and interpregnancy weight gain was associated with gestational diabetes mellitus (GDM; 88% greater risk), pre-eclampsia (92% greater risk) and large-for-gestational-age (36% greater risk) babies 5. A systematic review of 38 studies found a consistent association between maternal prepregnancy weight and offspring obesity 6.…”
Section: Introductionmentioning
confidence: 99%
“…In Nagpal et al, 1 an error was published in the last sentence of Section 3.2. The value was incorrectly defined as “BMI ≥ 25 kg/m 2 .” The sentence should have read:
Interpregnancy weight loss was associated with a significant reduction in GDM for BMI < 25 kg/m 2 (Figure 3B).
…”
mentioning
confidence: 99%